Avaliação das concentrações plasmáticas de dímero-d em vacas adultas e seus bezerros até 24 horas de idade: Maria Cecilia Borgo Murback. - - Murback, Maria Cecilia Borgo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The D-dimers are the smallest fragments of fibrin degradation products and are produced by plasmin after lysis of fibrin cross-connection. Thus, the objectives of this study were to determine plasma concentrations of D-dimer and fibrinogen in newborn calves and postpartum cows and to compare plasma concentrations of this hemostatic marker between these two groups. Significant increases in plasma concentrations of D-dimers occur during inflammatory processes (such as peritonitis, sepsis), disseminated intravascular coagulation and vena cava thrombosis for example. Plasma concentrations of D-dimer and fibrinogen were not different between groups. There was a significant positive correlation between plasma fibrinogen concentrations between groups. There was no correlation between plasma D-dimer between groups. Therefore, it was possible to establish reference intervals for plasma concentrations of D-dimer in postpartum cows and their newborn calves.
Keywords: Bovino; Sangue - Coagulação; Inflamação; Vaca; Bezerro; Dímeros; Fibrinogen